The Influence of Brand Ambassadors, Product Reviews, and Risk Perceptions on Purchasing Decisions at Tokopedia E-Commerce in Jakarta - Ayu Kusuma Puspitasari; Elwisam Elwisam; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2023)
This study aims to determine and analyze the effect of brand ambassador, product reviews, and risk perception on purchasing decisions on e-commerce Tokopedia customers in Jakarta. The research method used in this research is using quantitative methods. The sample in this study amounted to 96 respondents using the Purposive Sampling technique. The data collection technique in this study was using a questionnaire. The data analysis technique in this study is multiple regression, classical assumption test, hypothesis testing using SPSS 22 software. The research results concluded brands ambassador and risk perceptions were positive and significant in purchasing decisions through e-commerce Tokopedia. And product reviews were negative and not significant in purchasing decisions through e-commerce Tokopedia.